Combination Therapy in Experimental Chagas Disease: A Review - Pagotti, Mariana Cintra; Starling, Luiz Guilherme; Pinto Martins, William Luiz; de Souza, Lindamar Maria; Furtado, Luis Fernando Viana; Mazzeti, Ana Lia (Current Drug Research Reviews, 2025)
Chagas disease is a neglected tropical disease caused by the protozoan <span class=
Keywords: Chagas disease chemotherapy